Nano-SiO2 coating enabled uniform Na stripping/plating for dendrite-free and long-life sodium metal batteries. Issue 12 (25th November 2019) - Jiang, Fuyi; Li, Tianjiao; Ju, Peng; Sun, Jianchao; Liu, Chuang; Li, Yiwei; Sun, Xueqin; Chen, Chengcheng
Abstract : Metallic sodium, which has a suitable redox potential and high theoretical capacity, is regarded as an ideal anode material for rechargeable Na metal batteries. Abstract : Metallic sodium, which has a suitable redox potential and high theoretical capacity, is regarded as an ideal anode material for rechargeable Na metal batteries. However, dendrite growth on sodium metal during cycling has seriously restricted its practical applications. Herein, we employed a low-cost and facile brushing method to fabricate a porous nano-SiO2 coating, which can induce a relatively uniform distribution of Na + flux and suppress the growth of Na dendrites. The nano-SiO2 coating with high porosity can decrease the Na stripping/plating overpotential (<50 mV) over 400 cycles at 5 mA cm −2 . Moreover, when coupled with a Na3 V2 (PO4 )3 (NVP) cathode, the Na with SiO2 coating (Na@SiO2 ) composite anode shows a favorable suitability in a full cell. Compared with the one with a bare Na anode, the full cell with the Na@SiO2 anode delivers a 27.8% higher discharge capacity (94.6 vs. 74 mA h g −1 at 1C) after 1000 cycles.